How climate scientists and communication professionals view public engagement with science: Perspectives, practices and constraints - Oliveira, Liliana; Carvalho, Anabela (Frontiers in Communication, 2023)
This article examines understandings of public engagement in science by scientists and communicators in four universities in Portugal and Spain. Based on mixed-methods research, we present an integrative analysis of practices and perceptions of climate change scientists and communication professionals, and identify critical barriers for them to further public engagement. More similarities than differences are found between the four universities and the two countries but there are important differences between the two professional groups. Universities and the scientific community at large tend to privilege forms of science communication that are focused on dissemination of information and on self-promotion. Although several interviewees acknowledge a normative requirement of having citizens participate more deeply in science, they stay short of fulfilling such commitment. This may be partly due to implementation barriers but also because scientists and especially communication professionals make a relatively narrow reading of the potential benefits of engaging the public in science. Over the last decade there are signs of positive developments, even though some aspects of science communication practice appear to have worsened.